Chemically crosslinked hyaluronic acid-chitosan hydrogel for application on cartilage regeneration - Escalante, Sandra; Rico, Gustavo; Becerra, José; San Román, Julio; Vázquez-Lasa, Blanca; Aguilar, Maria Rosa; Durán, Iván; García-Fernández, Luis (Frontiers in Bioengineering and Biotechnology, 2022)
Articular cartilage is an avascular tissue that lines the ends of bones in diarthrodial joints, serves as support, acts as a shock absorber, and facilitates joint’s motion. It is formed by chondrocytes immersed in a dense extracellular matrix (principally composed of aggrecan linked to hyaluronic acid long chains). Damage to this tissue is usually associated with traumatic injuries or age-associated processes that often lead to discomfort, pain and disability in our aging society. Currently, there are few surgical alternatives to treat cartilage damage: the most commonly used is the microfracture procedure, but others include limited grafting or alternative chondrocyte implantation techniques, however, none of them completely restore a fully functional cartilage. Here we present the development of hydrogels based on hyaluronic acid and chitosan loaded with chondroitin sulfate by a new strategy of synthesis using biodegradable di-isocyanates to obtain an interpenetrated network of chitosan and hyaluronic acid for cartilage repair. These scaffolds act as delivery systems for the chondroitin sulfate and present mucoadhesive properties, which stabilizes the clot of microfracture procedures and promotes superficial chondrocyte differentiation favoring a true articular cellular colonization of the cartilage. This double feature potentially improves the microfracture technique and it will allow the development of next generation therapies against articular cartilage damage.